Объяснение:
a + b = 5; ab = 3
a^3*b^2 + a^2*b^3 = a^2*b^2*(a+b) = (ab)^2*(a+b) = 3^2*5 = 9*5 = 45
(a-b)^2 = a^2 + b^2 - 2ab = a^2 + 2ab + b^2 - 4ab = (a+b)^2 - 4ab = 5^2 - 4*3 = 13
a^4 + b^4
Здесь сложнее. Сначала найдем
a^2 + b^2 = a^2 + 2ab + b^2 - 2ab = (a+b)^2 - 2ab = 5^2 - 2*3 = 19
Теперь найдем
(a^2 + b^2)^2 = a^4 - 2a^2*b^2 + b^4 = a^4 + b^4 - 2(ab)^2
a^4 + b^4 = (a^2 + b^2)^2 + 2(ab)^2
Но мы знаем, что
(a^2 + b^2)^2 = 19^2 = 361.
Отсюда
a^4 + b^4 = (a^2 + b^2)^2 + 2(ab)^2 = 19^2 + 2*3^2 = 361 + 18 = 379
1) x^4 - 6x^2 + 8 = 0
x^4 - 6x^2 = - 8
x^2(x^2 - 6) = - 8
x^2 = - 8 или x^2 - 6 = -8
x^2 = - 8 x^2= - 8 + 6
x^2 = - 2
2) (2x - 1)^2 - (2x - 1) - 12 = 0
(2x - 1)^2 - (2x - 1 ) = 12
4x^2 - 4x + 2 - 2x + 1 = 12
4x^2 - 6x = 12 -1 -2
4x^2 - 6x = 9
2x ( 2x - 3) = 9
2x = 9 или 2x - 3 = 9
x = 9/2 2x= 9+3
x = 4,5 2x = 12
x = 6
Объяснение: